Mycobacterium tuberculosis Myositis Without Concurrent Pulmonary Symptoms in a Patient With Immunosuppression - Caroline Jansen; Kristin R.V. Harrington; Samuel Bennett; Nirisha Commodore; Joseph A. Behnke; Rebecca Steinberg; Matthew Carroll; Bryan Morales-Vargas; Malak Abedalthagafi; Ankit Agrawal; Ananth Vadde; Wassim Abdallah (Annals of Internal Medicine: Clinical Cases)
We describe a rare presentation of extrapulmonary tuberculosis in a patient with type 1 diabetes mellitus and dermatomyositis on immunosuppressive therapy. This case highlights important diagnostic considerations in particular patient populations and raises several interesting questions about the pathophysiology underlying this patient's complex disease presentation.